Regional destination image perception of tourists within a winescape context. Issue 2 (25th January 2017) - Bruwer, Johan; Pratt, Marlene A.; Saliba, Anthony; Hirche, Martin
Abstract : This study's purpose is to conceptualise a wine regional destination's perceived image, in the process integrating multiple theories such as servicescape, place-based and destination choice. The research ( n  = 334 respondents) outlines the conceptualisation of a wine region destination's image in the form of a winescape framework as perceived by visitors. The winescape construct is identified within a framework of eight dimensions for a well-known US wine region. The most important winescape dimension is the natural beauty/geographical setting. The first-time and repeat visit dynamic impacts upon visitors' wine tourism behaviour and perception of the region's winescape. For in-state and out-of-state-based visitors there are pronounced differences in their perception of the region's winescape dimensions. Increasing distance from the destination region is pivotal in the perception of the winescape dimensions. The decision to engage in wine tourism is seemingly impulsive from a timing viewpoint, and the motivations guiding the visitors' behaviour are mainly of a hedonic nature.